Analysis of the 'Educational Climate' in Spanish Public Schools of Dentistry using the Dundee Ready Education Environment Measure: a multicenter study. (30th January 2013) - Tomás, I.; Millán, U.; Casares, M. A.; Abad, M.; Ceballos, L.; Gómez‐Moreno, G.; Hidalgo, J. J.; Llena, C.; López‐Jornet, P.; Machuca, M. C.; Monticelli, F.; Palés, J.
Abstract Aim To analyse the 'Educational Climate' (EC) of dental students in Spain. Methods The study group consisted of 1391 students from nine Spanish Public Schools of Dentistry, who responded to the questionnaire based on 'Dundee Ready Education Environment Measure' (DREEM). This questionnaire has 50 items that are grouped into five domains: Learning, Teachers, Academic, Atmosphere and Social. Results The global score on the EC was 123.1 (interpretation: 'EC more positive than negative'). The scores obtained in the different domains were: 28.0 in Learning (interpretation: 'a generally positive perception of learning'), 26.8 in Teachers (interpretation: 'teachers are going in the right direction'), 20.8 in Academic (interpretation: 'feeling more on the positive side'), 29.7 in Atmosphere (interpretation: 'a generally positive atmosphere') and 17.7 in Social (interpretation: 'social perception acceptable'). In seven items (14%), an average of <2 was detected, showing that there are some educational problem areas. Regarding the EC in the different Schools of Dentistry, an average of >100 was achieved in all of them, although there were two centres that showed significantly higher values of EC. Conclusions Spanish dental students felt that their EC was more positive than negative and considered that the different domains were positive and acceptable. However, they pointed out the existence of several educational problem areas associated with the development of a traditional curriculum. Accordingly, and in parallel with the implementation of an innovative curriculum in all Spanish Dental Schools in the coming years, immediate educational goals must address the problem areas identified, thereby further promoting a more positive perception of EC.